Macromyzus Takahashi (Hemiptera, Aphididae), a generic account, description of one new species, and keys to species - Su, Xiao-Mei; Qiao, Ge-Xia (Zootaxa, 2010)
The aphid genus Macromyzus Takahashi is reviewed, and keys to known species provided. Macromyzus spinosus sp. nov. is described from Plagiogyria japonica in Hunan, China. Macromyzus (Anthracosiphoniella) maculatus (Basu) is recorded for the first time in China. The type specimens are deposited in the National Zoological Museum of China, Institute of Zoology, Chinese Academy of Sciences, Beijing, China.